Induction of Motor Associative Plasticity in the Posterior Parietal Cortex-Primary Motor Network - Chao, C.-C.; Karabanov, A. N.; Paine, R.; Carolina de Campos, A.; Kukke, S. N.; Wu, T.; Wang, H.; Hallett, M. (Cerebral cortex (New York, N.Y. 1991), 2015)
There is anatomical and functional connectivity between the primary motor cortex (M1) and posterior parietal cortex (PPC) that plays a role in sensorimotor integration. In this study, we applied corticocortical paired-associative stimuli to ipsilateral PPC and M1 (parietal ccPAS) in healthy right-handed subjects to test if this procedure could modulate M1 excitability and PPC-M1 connectivity. One hundred and eighty paired transcranial magnetic stimuli to the PPC and M1 at an interstimulus interval (ISI) of 8 ms were delivered at 0.2 Hz. We found that parietal ccPAS in the left hemisphere increased the excitability of conditioned left M1 assessed by motor evoked potentials (MEPs) and the input-output curve. Motor behavior assessed by the Purdue pegboard task was unchanged compared with controls. At baseline, conditioning stimuli over the left PPC potentiated MEPs from left M1 when ISI was 8 ms. This interaction significantly attenuated at 60 min after left parietal ccPAS. Additional experiments showed that parietal ccPAS induced plasticity was timing-dependent, was absent if ISI was 100 ms, and could also be seen in the right hemisphere. Our results suggest that parietal ccPAS can modulate M1 excitability and PPC-M1 connectivity and is a new approach to modify motor excitability and sensorimotor interaction.